Generalized anxiety disorder associated with individual work performance of Indonesian medical personnel during COVID-19 outbreak - Eko Sujadi; Muhammad Fadhli; Muhd. Odha Meditamar; Dairabi Kamil; Ahmad Jamin; Hengki Yandri; Syaiful Indra (International Journal of Public Health Science (IJPHS), 2021)
Coronavirus disease (COVID-19) outbreak has the potential to affect the mental health of medical personnel. This study aimed to investigate the anxiety experienced by medical personnel during the COVID-19 outbreak and its correlation with individual work performance. A cross-sectional study was conducted on 501 Medical Personnel in Indonesia. Anxiety level and work performance were assessed by the GAD-7 and IWP-1.0. Data analysis techniques used were descriptive statistics, Man-Whitney test, Kruskal-Wallis test, and Spearman's Rank-Order Correlation. The results showed that 33.33% of the participants did not experience anxiety, followed by moderate, mild, and severe levels (31.14%, 27.74%, and 7.78%). Furthermore, the level of anxiety was different in terms of sex, age, and type of medical personnel, while there was no difference in the length of time of work. The results of the correlation analysis showed that anxiety was correlated with task performance and contextual performance, but there was no correlation with the counter-productive work behavior. There is a crucial need for psychological assistance to medical personnel in orders to reduce their anxiety as well as improve their performance.